2016
DOI: 10.1051/sicotj/2016027
|View full text |Cite
|
Sign up to set email alerts
|

Minimal important difference after hand surgery: a prospective assessment for DASH, MHQ, and SF-12

Abstract: Introduction: Minimal important difference (MID) score is an important measure for surgical clinical research and impacts on treatment decisions. Our approach considered patient satisfaction as the relevant anchor criteria. The aims of this study were: determine after surgery MID for three relevant questionnaires: Disabilities of the Arm, Shoulder and Hand (DASH), Michigan Hand Questionnaire (MHQ), and Short Form 12 (SF-12); and assess the correlation between these scores and patient reported satisfaction. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 13 publications
2
17
0
2
Order By: Relevance
“…These values are similar to our MIC of 16. In contrast, MIC thresholds for the brief and original MHQ total score range from 7 to 15 for patients with various hand disorders (London et al., 2014; Maia et al., 2016; Rodrigues et al., 2015, 2017; Wehrli et al., 2016). Our higher value can be explained by the varied effectiveness of TMC surgery, which presumably provides greater symptom relief in patients with worse baseline symptoms than in the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are similar to our MIC of 16. In contrast, MIC thresholds for the brief and original MHQ total score range from 7 to 15 for patients with various hand disorders (London et al., 2014; Maia et al., 2016; Rodrigues et al., 2015, 2017; Wehrli et al., 2016). Our higher value can be explained by the varied effectiveness of TMC surgery, which presumably provides greater symptom relief in patients with worse baseline symptoms than in the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Changes exceeding this value can be considered relevant for the patient. Several studies have investigated MIC for various outcome measures in hand surgery (London et al., 2014; Maia et al., 2016; Marti et al., 2016; Marks et al, 2019; Rodrigues et al., 2015, 2017; Shauver and Chung, 2009; Wehrli et al., 2016). For patients with trapeziometacarpal (TMC) osteoarthritis (OA), however, the MIC has only been determined for the Michigan Hand Outcomes Questionnaire (MHQ, Marks et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Higher scores indicate less disability. Both the primary English MHQ and the official Dutch translation have good psychometric properties [8,[33][34][35][36][37][38].…”
Section: Measurementsmentioning
confidence: 99%
“…The finding that SF-12 physical and mental component scores were not related to changes in the other patient-rated scores is not unique to our study. Maia et al 22 also noted this in relation to upper extremity conditions and suggested that the SF-12 is too broad in its assessment of individuals to pick up changes where region or diseasespecific changes are being assessed.…”
Section: Discussionmentioning
confidence: 99%